2000
DOI: 10.1055/s-2000-19256
|View full text |Cite
|
Sign up to set email alerts
|

Osteosynthesen mit resorbierbaren Hemizerklagen bei Metakarpalfrakturen*

Abstract: The use and results of biodegradable hemicerclages for metacarpal fracture fixation were reviewed retrospectively. A total of 92 metacarpal fractures in 78 patients were treated with polyglycolic or polydioxanon sutures. Study parameters included time for bony union, duration of immobilisation, total active range of motion, and complications. The hemicerclage achieved rigid fracture fixation and permitted early mobilisation exercises without jeopardizing bony union. Immobilization of metacarpals was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…This required open reduction and a combination of cerclage wires and a wrist splint for 3 weeks [31]. The use of absorbable hemi-cerclage sutures needed 1.5-6 weeks immobilization and led to one redisplacement in 92 (combination of types) fractures [32].…”
Section: Discussionmentioning
confidence: 99%
“…This required open reduction and a combination of cerclage wires and a wrist splint for 3 weeks [31]. The use of absorbable hemi-cerclage sutures needed 1.5-6 weeks immobilization and led to one redisplacement in 92 (combination of types) fractures [32].…”
Section: Discussionmentioning
confidence: 99%
“…user et al, 1999;Krein et al, 2000;Meyer-Clement et al, 1984). PGA or PDS sutures (2/0 USP) have been used to fix 92 metacarpal fractures in 78 patients.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…One fracture redisplacement occurred, and the authors concluded that this method is suitable for the treatment of oblique and spiral fractures (Br . user et al, 1999;Krein et al, 2000). Rustemeier and Ganmann (1986) reported five cases of avulsion fracture of the extensor tendon, which were fixed with two 1.0 mm non-SR PDS pins and sutures.…”
Section: Clinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation